Syed Abdullah Brelvi Road - Ghosh, Ayan (2023)
The Bombay Samachar office is located on SA Brelvi Road, named after Syed Abdullah Brelvi, long-time editor of the Bombay Chronicle. Brelvi joined the newspaper as an assistant editor in 1915 and became editor in 1924, a position he held till his death (1949). He supported Mahatma Gandhi and critiqued the Muslim League, which irritated M.A. Jinnah.